2022
DOI: 10.26434/chemrxiv-2022-sd6bg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioaccessibility of organic compounds associated with tire particles using a fish in vitro digestive model: solubilization kinetics and effects of food co-ingestion

Abstract: Tire and road wear particles (TRWP) account for an important part of the polymer particles released into the environment. There are scientific knowledge gaps as to the potential bioaccessibility of chemicals associated with TRWP to aquatic organisms. This study investigated the solubilization and bioaccessibility of seven of the most widely used tire-associated organic chemicals and four of their degradation products from cryogenically milled tire tread (CMTT) into fish digestive fluids using an in vitro diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
3
1
Order By: Relevance
“…Tyre particles leach a cocktail of trace metals and organic pollutants (Halsband et al, 2020), which may cause digestive cell loss. In this present study, we were not able to discriminate between any effects of leachates as compared with the tyre particles themselves, although studies by Masset et al (2021Masset et al ( , 2022 found that heavy metals and organic compounds leach from the tyre particles into the gastrointestinal fluids of fish, backing up this theory.…”
Section: Oxidative Stresscontrasting
confidence: 71%
See 1 more Smart Citation
“…Tyre particles leach a cocktail of trace metals and organic pollutants (Halsband et al, 2020), which may cause digestive cell loss. In this present study, we were not able to discriminate between any effects of leachates as compared with the tyre particles themselves, although studies by Masset et al (2021Masset et al ( , 2022 found that heavy metals and organic compounds leach from the tyre particles into the gastrointestinal fluids of fish, backing up this theory.…”
Section: Oxidative Stresscontrasting
confidence: 71%
“…Aquatic exposure affects growth and swimming behaviour in estuarine species; the springtail Menidia beryllina and the mysid shrimp Americamysis bahia (Siddiqui et al, 2022). As well as the physical effects caused by ingestion of particles, tyre wear particles can exert chemical effects through leaching of a cocktail of organic additives and metals into the surrounding water column and sediments (Halsband et al, 2020), or directly from the particles into the gastrointestinal fluids or organisms, as has been observed in fish (Masset et al, 2022;Masset et al, 2021). Leachates, with the particles removed, have proved lethal to marine copepods with an LC 50 of 35 g.L − 1 for Calanus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, RDC concentrations in shoe sole samples were highly variable and likely due to different compounding strategies used by manufacturers as well as the target product characteristics (i.e., stiffness, durability, performance, adhesiveness). RDC concentrations in shoe sole samples were generally lower (DPG and PPDs) or similar (benzothiazoles) to those in tire tread 51,52 but higher than in other elastomeric consumer products 52 .…”
Section: Engineered Climbing Shoes Contain High Quantities Of Rubber-...mentioning
confidence: 79%
“…These results suggest that, as in other rubber products, 2SH-BTZ is used as a vulcanization accelerator during the curing process. Other benzothiazoles are also present and are typically considered to be impurities or degradation products 51,52 . Unlike benzothiazoles, DPG and aniline were not detected in every shoe sole sample, with concentrations ranging from <LOQ to 814 µg/g and <LOQ to 225 µg/g, respectively.…”
Section: Engineered Climbing Shoes Contain High Quantities Of Rubber-...mentioning
confidence: 99%